Exploring the academic and psychosocial impact of El Sistema-inspired music programs within two low socio-economic schools. (2nd April 2016) - Osborne, Margaret S.; McPherson, Gary E.; Faulkner, Robert; Davidson, Jane W.; Barrett, Margaret S.
Abstract : We sought to understand the potential for positive non-musical outcomes for economically and socially disadvantaged primary school students who are involved in instrumental music learning programs. Two schools with students experiencing generational poverty, current or first-generation immigrant or refugee status who were running El-Sistema inspired music programs participated in the study. Ninety-two students in Years 3–6 completed audio-visual assessments of non-verbal reasoning, verbal and mathematical ability, and psychosocial well-being. Comparisons by school and program participation over a period of 12 months, indicate improved non-verbal (visuo-spatial) reasoning, verbal and mathematical skills, and psychosocial well-being for students at School 1. Findings indicate some evidence of positive outcomes for low socio-economic status and socially disadvantaged children who participate in El Sistema-inspired extra-curricular music programs. Given the substantial number of students involved in such programs worldwide, these findings suggest outcomes for disadvantaged students may be improved through music learning opportunities.